How much do top management teams matter in founder‐led firms? - Hendricks, Bradley E.; Howell, Travis; Bingham, Christopher B. (Strategic Management Journal, 2019)
Research Summary As firms mature, their founders are often replaced with seasoned executives. When founders are retained, the surrounding top management team (TMT) members are viewed as critical resources in helping compensate for the founder's managerial deficiencies. Surprisingly, however, little is known about how TMT members affect a founder‐led firm's performance later in a firm's life. Using novel methods and a sample of over 2,000 firms, we address this gap. We find that although team structure has a significant impact on the performance of nonfounder‐led firms (consistent with past literature), it has little to no effect on the operating performance of founder‐led firms, suggesting that founder chief executive officers (CEOs) may exert too much control. Thus, the irony is that founders are retained to propel progress but their very retention may prevent progress. Taken together, our findings add to the entrepreneurship, team, and research methods literatures. Managerial Summary Although founders have the entrepreneurial skills to successfully grow a startup, they generally lack the managerial skills required to lead a large, public firm. As a result, many founder CEOs are replaced before a firm goes public. When founders do stay as CEO, the prevailing belief is that they require a strong TMT to help compensate for the founder's managerial deficiencies. However, given founders' desire to retain control, there is a question of whether they will rely on that team, or if they will simply continue to follow their own intuition. We find evidence that founder CEOs are much less likely to listen to and benefit from their teams relative to nonfounder CEOs.